Gut microbiota correlates with antitumor activity in patients with mCRC and NSCLC treated with cetuximab plus avelumab. Issue 3 (29th April 2022) - Martini, Giulia; Ciardiello, Davide; Dallio, Marcello; Famiglietti, Vincenzo; Esposito, Lucia; Corte, Carminia Maria Della; Napolitano, Stefania; Fasano, Morena; Gravina, Antonietta Gerarda; Romano, Marco; Loguercio, Carmelina; Federico, Alessandro; et al.
Abstract: Gut microbiota is involved in immune modulation and immune checkpoint inhibitors (ICIs) efficacy. Single‐arm phase II CAVE‐mCRC and CAVE‐LUNG clinical trials investigated cetuximab + avelumab combination in RAS wild‐type (WT) metastatic colorectal cancer (mCRC) and chemo‐refractory nonsmall cell lung cancer (NSCLC) patients, respectively. A comprehensive gut microbiota genetic analysis was done in basal fecal samples of 14 patients from CAVE‐mCRC trial with circulating tumor DNA (ctDNA) RAS/BRAF WT and microsatellite stable (MSS) disease. Results were validated in a cohort of 10 patients from CAVE‐Lung trial. 16S rRNA sequencing revealed 23 027 bacteria species in basal fecal samples of 14 patients from CAVE‐mCRC trial. In five long‐term responding patients (progression‐free survival [PFS], 9‐24 months) significant increases in two butyrate‐producing bacteria, Agathobacter M104/1 ( P = .018) and Blautia SR1/5 ( P = .023) were found compared to nine patients with shorter PFS (2‐6 months). A significantly better PFS was also observed according to the presence or absence of these species in basal fecal samples. For Agathobacter M104/1, median PFS (mPFS) was 13.5 months (95% confidence interval [CI], 6.5‐20.5 months) vs 4.6 months (95% CI, 1.8‐7.4 months); P = .006. For Blautia SR1/5, mPFS was 5.9 months (95% CI, 2.2‐9.7 months) vs 3.6 months (95% CI, 3.3‐4.0 months); P = .021. Similarly, in CAVE‐Lung validation cohort, Agathobacter M104/1 and Blautia SR1/5 expression were associated with PFS according to their presence or absence in basal fecal samples. Agathobacter and Blautia species could be potential biomarkers of outcome in mCRC, and NSCLC patients treated with cetuximab + avelumab. These findings deserve further investigation. Abstract : What's new? The gut microbiota has been proposed as a relevant player in cancer development as well as a potential modulator of sensitivity to immunotherapy. Here, the authors performed an extensive analysis of pretreatment fecal microbiota species in patients with metastatic colorectal cancer and nonsmall cell lung cancer treated with cetuximab plus avelumab in the CAVE‐mCRC and CAVE‐lung trials, respectively. For the first time, they demonstrate that two gut bacteria species are associated with longer progression‐free survival. The two butyrate‐producing bacteria could become potential biomarkers for cetuximab plus avelumab antitumor activity in chemo‐refractory colorectal cancer and nonsmall cell lung cancer patients.